Dilemmas of Brazilian schooling policies in the early 21st century: democratization, citizenship and social justice - Roberto Rafael Dias da Silva; Rodrigo Manoel Dias da Silva (Universidade Estadual de Maringá, 2015)
This analysis is foregrounded on schooling policies in Brazil, especially with regard to the investigation of some dilemmas conceived as a challenge to these policies. A theoretical study produced a diagnosis on the relationship between education, citizenship and social justice as factors that reorganize the agenda of educational policies at the beginning of the 21st century. A documentary study identifies and interprets three political dilemmas that make up Brazil's policies for expanding the school schedule, by establishing equity as a principle, protection as a goal and intersectionality as a policy.